Company Income Tax, Custom and Excise Duties: A Prelude for Nigerian Economic Growth Using ARDL Approach - Bakare, Taophic Olarewaju; Akindele, Jamiu Adeniyi; Babansulaiman, Abdulganiyu; Adegboyega, Ayodeji Hakeem (Universitas Syiah Kuala, 2024)
Objective The main objective of this paper is to examine the effects of company income tax, customs and excise duties, and economic growth in Nigeria.Design/Methodology The study used Auto Regressive Distributed Lag and the study covered the period between 1982 2022 with the aid of ex-post facto research design.Research limitations/implications The study is limited to tax revenue precisely custom and excise duties and company income tax using times series analysis. The implications of this study are that in order to significantly enhance revenue inflows from excise duties and CIT source, the report advises the government focus on expanding the tax base rather than raising the rate of corporate income tax.Findings The results found that company income tax has positive and significant effect on economic growth in Nigeria with the coefficient 1.1532 and p-value 0.000 while custom and excise duties revealed negative but significant effect with the coefficient -0.1315 and p-value 0.010 on economic growth in Nigeria.Novelty/Originality The originality of this research lies in the methodology of the study where previous studies analysed the data through econometric techniques such as FMOLS and Johansen co-integration techniques which do not provide for the accommodation of small samples, ARDL method used by this study yields statistically significant results in small samples. More also, ARDL technique yields unbiased and dependable estimates of the long-run model. That makes this study a unique and contribution to the body of knowledge.